Implementasi Metode Regresi Linear Berganda untuk Mengatasi Pelanggaran Asumsi Klasik - Mei Dian Irrawati; Maya Mukaramah (Penerbit Goodwood, 2024)
Purpose: This study investigates the impact of economic events, such as recessions, on the classical assumptions that form the basis of economic theory. Exploring the applicability of classical economic theory assumptions by considering real-world deviations during economic events. Methodology/approach: The Research Methodology utilizes successful journal and interval review methods to examine economic events and their impact on classical economic theory. Apply the multiple linear regression test to predict the value of the dependent variable using known independent variables. The confidence interval method was employed to estimate the precision of the statistical parameters. Results/findings: Results and present findings on the deviation from classical assumptions during economic events. This study provides insights into the predictive power of multiple linear regressions in the context of economic instability. Share the estimated values and precision of the statistical parameters using the confidence interval method. Limitations: We acknowledge the limitations related to the generalization of the findings during economic events. Recognize the inherent challenges of applying classical economic assumptions to real-world scenarios. Contribution: Contributes to the development of economic theory by highlighting discrepancies between classical assumptions and the complexities of economic events.